활성산소종이 무궁화 꽃의 노화에 미치는 영향 - 서상규(Sang Gyu Seo); 김선형(Sun Hyung Kim); 이긍표(Gung Pyo Lee); 강승원(Seung Won Kang) (Journal of plant biotechnology, 2009)
To understand the effect of reactive oxygen species (ROS) on floral senescence in Hibiscus syriacus L., we have investigated change in relative water potential, malondialdehyde (MDA) content, H_2O_2 content and the activity of antioxidative enzymes in the petals during flower opening and senescence. Hibiscus flowers were achieved full bloom at early morning and started to in-rolling and showed petal in-rolling over than 50% at 24 h and 36 h after full bloom, respectively. The flower was a decrease in fresh weight by 30% and showed water loss with floral senescence. MDA content and activity of antioxidative enzymes such as APX, GR and CAT were showed no significant change until 36 h after full bloom. In the flower 48 h after full bloom that showed complete petal in-rolling and wilting, however, activity of antioxidative enzymes and H_2O_2 content was greatly increased as compared with 0 h after full bloom. These results suggest that reactive oxygen species are related to accelerating the later senescence more than inducing the early senescence during Hibiscus flower senescence.